Theme of Gender in Toni Morrison's the Bluest Eyes and Sula - Abdullah, Nibras Ahmed (جامعة تكريت - كلية الآداب, 2019)
تتناول هذه الدراسة الروائية الافروأمريكية توني موريسون. لتكشف القضايا المتعلقة بنوع الجنس والتي تتجلى بوضوح في حياتها وأعمالها. لبيان قلق موريسون لإحباط السيدات في نظر العامة. وهي عبارة عن بطلتين إناث تم تصورهما وتربيتا حسب المعايير وحالة من الميول الجنسية والجنس والحب الذي يشكل هويتهما. يتحدث الأبطال الأنثويون بيكولا وسولا إلى تقييمين متميزين وأطر ذهنية تجاه الوظائف الجنسية والجنس والحب. فيما يتبع نيل المعايير العرفية للمجتمع؛ في حين ترفض سولا الأفكار التقليدية من "الواجب" المهذب وترفض اعتبار السيدات مجرد أزواج وأمهات. هذا البحث بالإضافة إلى توضيح كيفية هذه المعايير وحالة التوجه الجنسي والجنس.
This study deals with Afro-American women novelist namely Toni Morrison. She explores “issues related to Gender which are clearly manifested in their lives and works. This "work" is a statement of Morrison's "anxiety" for "the debasement of ladies in the public eye. It is around "two" female heroes who have been conceived and raised by standards and a situation of sexual orientation, "sex" and love that shape their identities. “The female heroes Pocola and Sula speak to two distinct assessments and frames of mind toward sex jobs, sex "and" love. Pocola pursues the customary standards of society; while Sula for a mind-blowing duration rejects the conventional ideas “of ladylike 'duty' and declines to consider ladies to “be just spouses and moms. This paper additionally clarifies“ how these standards and condition of sexual orientation, sex.
Keywords: الرواية -- الحب -- الجنس -- المجتمع الأمريكي -- رواية العين الأشد زرقة -- موريسون، توني، ت. 2019 م